Impact of prolonged social crisis on resilience and coping indicators. - Hadas Marciano; Shaul Kimhi; Yohanan Eshel; Bruria Adini (PLoS ONE)
The current study examines, longitudinally, (i.e., on the same sample), to what extent an acute political/social crisis in Israel affected the resilience, distress, and additional psychological indicators of the Jewish population, along with three repeated measurements: The first was conducted shortly before the last elections (in October 2022), the second in February 2023, about two and a half months after the elections, following the formation of a right-wing government, and the third measurement about nine months after the election (August 7-10, 2023). The main results indicated the following: (a) the mean societal resilience among coalition voters increased significantly throughout the three measurements, while it declined significantly among opposition voters. (b) significant differences were identified between coalition and opposition voters, mostly at T2 and T3: opposition supporters reported significantly lower levels of societal resilience and hope, and higher levels of distress symptoms and sense of danger, compared to those of coalition supporters. We concluded that the continued social/political conflict in Israel is multidimensional and impacts diverse areas such as values, perspectives, and supporting as well as suppressing coping indicators. The differences between the two voter groups may be primarily the result of political radicalization and polarization processes, that aim to widen gaps to achieve political power. As many countries are currently facing acute political crises and similar radicalization, similar studies should be conducted in varied societies to investigate the generalizability of the findings.